Engaging undergraduate students in synchronous online courses: challenges and strategies - Kocabas, Hatice Uslu; Bavli, Bunyamin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Synchronous online courses (SOC), enabling real-time interaction, have become increasingly prevalent in higher education, particularly during emergency remote teaching (ERT). This surge in online education raised questions about how student engagement, a crucial factor for the quality of higher education practices, was achieved during ERT. To address these questions and offer insights into effective practices for fostering student engagement in SOC, this study explores the experiences of undergraduate students and instructors during ERT. While a substantial body of literature addresses student engagement, there is a gap in studies that comprehensively synthesize effective practices to engage undergraduate students in SOC across various departments. Therefore, the present study seeks to bridge this gap. Insights were gathered through semi-structured one-on-one interviews and a focus group with ten instructors and fifteen students across diverse departments and universities. The study findings unveil effective strategies and practices to promote student engagement in SOC. These strategies closely align with the elements of teaching, social, and cognitive presence within the Community of Inquiry (CoI) framework, emphasizing interaction-based pedagogical practices and the role of emotional communication in SOC. The study not only provides valuable strategies for enhancing student engagement during crises but also highlights their relevance in normal times.
Keywords: Synchronous online courses; remote teaching; student engagement; online engagement; community of inquiry; ENGAGEMENT; CLASSROOM; IMPACT; COLLABORATION; PERCEPTION; COMMUNITY; EDUCATION; INQUIRY; SUPPORT; Education & Educational Research